2002
DOI: 10.1029/2001ja009224
|View full text |Cite
|
Sign up to set email alerts
|

Global hybrid simulation of the Kelvin–Helmholtz instability at the Venus ionopause

Abstract: [1] The Kelvin-Helmholtz (K-H) instability at the Venus ionopause is investigated using a two-dimensional global hybrid (particle ions, massless fluid electrons) model for the case where the interplanetary field is oriented transverse to the flow. In order to selfconsistently study the kinetic processes at the Venus ionopause, we calculate the entire Venus ionopause-solar wind interaction region kinetically, including the ionosphere, ionopause transition layer, magnetosheath, and solar wind regions, by applyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
159
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 139 publications
(164 citation statements)
references
References 92 publications
5
159
0
Order By: Relevance
“…The observations presented here also demonstrate that conditions are favorable for the generation of KHI at the ionopause. Hybrid simulations of the KHI by Terada et al [2002] have shown the existence of large filaments or streamers of plasma within the magnetosheath. These filaments tend to occur at all SZAs in the hemisphere in which the motional electric field possesses a component pointing away from the planet, while in the case when the electric field is directed downward the filaments were observed only at high SZA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The observations presented here also demonstrate that conditions are favorable for the generation of KHI at the ionopause. Hybrid simulations of the KHI by Terada et al [2002] have shown the existence of large filaments or streamers of plasma within the magnetosheath. These filaments tend to occur at all SZAs in the hemisphere in which the motional electric field possesses a component pointing away from the planet, while in the case when the electric field is directed downward the filaments were observed only at high SZA.…”
Section: Discussionmentioning
confidence: 99%
“…Hence these observations took place in the E up hemisphere, which, as mentioned above, may result in the formation of filamentary structures [Terada et al, 2002].…”
Section: Observations On 3 June 2006mentioning
confidence: 99%
See 3 more Smart Citations